2019
DOI: 10.1037/pag0000352
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in cue utilization during prospective and retrospective memory monitoring.

Abstract: Memory monitoring is an inferential process that we use to evaluate and make judgments about the contents of our memory. Prior work has shown age-related similarity in prospective monitoring of ongoing memory processes, but age-related deficits when retrospectively monitoring the source of memories. In the current study, we examined how extrinsic and intrinsic cues influence age differences in these two forms of memory monitoring. Two experiments were conducted in which young and older adults made prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…For instance, Nomi et al (2013) found no difference in JOLs for faces with positive or negative expressions. Consistent with Nomi et al's (2013) findings, other studies found no statistically detectable difference using other types of learning materials, such as word lists (Gallant et al, 2019), word pairs (Zimmerman & Kelley, 2010) and images (Witherby, 2019).…”
Section: Emotionality and Jolssupporting
confidence: 64%
“…For instance, Nomi et al (2013) found no difference in JOLs for faces with positive or negative expressions. Consistent with Nomi et al's (2013) findings, other studies found no statistically detectable difference using other types of learning materials, such as word lists (Gallant et al, 2019), word pairs (Zimmerman & Kelley, 2010) and images (Witherby, 2019).…”
Section: Emotionality and Jolssupporting
confidence: 64%
“…At least for younger adults, this was in line with our hypothesis and replicates our prior work (Bowen, Gallant, et al, 2020) as memory was enhanced by the high-value reward cue, regardless of the subsequent memory instructions. The fact that older adults did not show this same pattern was unexpected as many studies in the literature have indicated that older adults are able to encode and remember high-value information better than low-value across a variety of experimental paradigms (Bowen, Ford, et al, 2020; Castel et al, 2002; Cohen et al, 2014; Gallant et al, 2019; Hennessee et al, 2017; Mather & Schoeke, 2011; Spaniol et al, 2014) including our prior directed forgetting studies (Bowen, Gallant, et al, 2020). Importantly, age did not moderate overall memory sensitivity or the false alarm rate, indicating that response bias is likely not driving the pattern of memory results.…”
Section: Methodsmentioning
confidence: 77%
“…Amid matching cues, consumers can automatically connect memory units for cognition and feedback. In addition, prospective memory (Gonzalez and Buchanan, 2019), retrospective memory (Bays and Taylor, 2018), implementation intentions (Liu et al , 2018), cue utilization (Gallant et al , 2019) and other theories closely correlate with contextual cues theory. In a highly interconnected business intelligence society, the richness and complexity of contextual cues affect the user experience of automation for sales, marketing, and service.…”
Section: Literature Reviewmentioning
confidence: 81%